2003
DOI: 10.1016/s0079-6425(02)00002-6
|View full text |Cite
|
Sign up to set email alerts
|

Durability of nanosized oxygen-barrier coatings on polymers

Abstract: Research on silicon oxide thin films developed as gas-barrier protection for polymer-based components is reviewed, with attention paid to the relations between (i) coating defects, cohesive strength and internal stress state, and (ii) interfacial interactions and related adhesion to the substrate. The deposition process of the oxide from a vapor or a plasma phase leads in both cases to the formation of covalent bonds between the two materials, with high adhesion levels. The oxide coating contains nanoscopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
351
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 472 publications
(360 citation statements)
references
References 291 publications
(381 reference statements)
9
351
0
Order By: Relevance
“…In recent years, there have been several investigations dealing with the mechanical failure of inorganic barriers. [5][6][7] As reported in literature, stressinduced cracking is the dominant reason for mechanical failure in barrier layers and subsequent device degradation. The cracking phenomenon is influenced by many factors, such as defect size and location, 5,7-9 internal stress, 10,11 layer thickness, 12,13 and loading type.…”
Section: Introductionmentioning
confidence: 84%
“…In recent years, there have been several investigations dealing with the mechanical failure of inorganic barriers. [5][6][7] As reported in literature, stressinduced cracking is the dominant reason for mechanical failure in barrier layers and subsequent device degradation. The cracking phenomenon is influenced by many factors, such as defect size and location, 5,7-9 internal stress, 10,11 layer thickness, 12,13 and loading type.…”
Section: Introductionmentioning
confidence: 84%
“…In this test the development of crack patterns was analyzed as a function of strain in-situ in a microscope in order to resolve the damage state in layers with sub-micrometer thickness [18,19]. Rectangular samples, of gauge length equal to either 16 mm or 40 mm and width equal to 5.5 mm, were carefully cut from the foils along θ =0°, 30°, 45°, 60°and 90°directions using a scalpel.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…50 MPa). Such very high levels of adhesion suggest that the behavior of the interfacial region is strain hardening and therefore prevents delamination [20], thanks to a high density of covalent bonds formed during plasma deposition [6].…”
Section: Coating Cohesive Strength and Coating/substrate Interfacial mentioning
confidence: 99%
“…Layered materials based on such thin film structures enable extremely low gas permeability, which could be suitable for advanced applications in the field of polymer-based displays [2]. A number of recent studies have shown that the defect structure of the coating control the oxygen and water vapor permeability of the coated film [3,4], as also its mechanical behavior such as cohesive and adhesive properties [5][6][7][8]. Nanosized oxide coatings are characterized by the presence of two types of defects, namely microdefects and nanodefects [3].…”
Section: Introductionmentioning
confidence: 99%